Training load, official match locomotor demand, and their association in top-class soccer players during a full competitive season - Riboli, A.; Nardi, F.; Osti, M.; Cefis, M.; Tesoro, G.; Mazzoni, S. (The Journal of Strength and Conditioning Research, 2025)
To examine training load and official match locomotor demands of top-class soccer players during a full competitive season and to evaluate their association. Twenty-five top-class soccer players competing in UEFA international competitions were included. The season was divided into 2 different categories: 2 matches (M2) or 3 matches (M3) in 8 days. Starters and nonstarters were classified. Total distance (TD), high-speed running (HSR, 15-20 km·h-1), very high-speed running (VHSR, 20.1-24 km·h-1), sprint (SPR, >24.1 km·h-1), and accelerations/decelerations (Acc + Dec, >3 m·s2) were recorded. Trivial to moderate differences (p < 0.05) in training load between M2 and M3 were found: HSR, VHSR, and SPR were higher in M2 than M3, whereas TD and Acc + Dec were higher in M3 than M2. Week-by-week variability in training load ranged from ~16 to ~59% depending on metrics. Official match locomotor demands were similar (p > 0.05) in M2 and M3 with ~5 to ~29% match-to-match variability depending on metrics. Total load (i.e., training plus match loads) was higher (p < 0.05, ES: 0.75/1.61) in starters than nonstarters, because of a higher match load and no difference in the training load. Very high-speed running and SPR accumulated during training sessions were largely to very largely (r = 0.60 to 0.72) associated with TD, HSR, VHSR, and Acc + Dec covered during official match; VHSR and TD during training were largely to very largely (r = 0.57 and 0.71) associated with SPR and Acc + Dec during official match. In conclusion, (a) congested periods seemed to not affect official match locomotor performance; (b) practitioners may consider high week-by-week workload variability for individualizing training prescriptions, especially for nonstarters; and (c) the VHSR and SPR accumulated during training were associated with the official match locomotor demands, and it may be considered for maximizing performance.